Analysis of Factors Affecting Budget Deficit in Indonesia - Prassoga, Tyo; Soebagiyo, Daryono (Gorontalo State University, 2025)
This study analyzes the factors influencing Indonesia's budget deficit during 1996-2023. The method used in this study is Ordinary Least Square (OLS) regression. The dependent variable in this study is the budget deficit, while the independent variables include Gross Domestic Product (GDP), foreign exchange reserves, exchange rates, inflation, and Indonesia's state debt. The study results indicate that gross domestic product (GDP), inflation, and government debt do not significantly affect the budget deficit in Indonesia. In contrast, the foreign exchange reserves and exchange rate variables have a positive and significant effect on foreign exchange reserves, meaning that an increase in these variables tends to increase the budget deficit. By understanding the factors that influence the budget deficit, it is hoped that the government can take more effective steps in maintaining the country's fiscal and economic stability.